Recent updates in the VERDI fission-fragment spectrometer - Gómez L A. M.; Al-Adili A.; Tarrío D.; Solders A.; Pomp S.; Vidali M.; Fontana C.L.; Geerts W.; Macías M.; Bonaldi C.; Oberstedt A.; Oberstedt S. (EPJ Web of Conferences)
The VElocity foR Direct particle Identification (VERDI) is a spectrometer designed to determine fission-fragment mass distributions using the 2E-2v method, which measures both velocities and energies of the fission fragments. VERDI has two time-of-flight (TOF) sections, each with a Micro Channel Plate (MCP) Time-of-flight Start detector and up to 32 passivated implanted planar silicon (PIPS) detectors. Achieving the desired mass resolution is challenged by the need for high TOF and energy resolutions. Recent upgrades to the VERDI setup have improved its performance, achieving a TOF resolution as low as 355 ps (FWHM) and an energy resolution of 22 keV (FWHM) for α-particles. These enhancements in resolution demonstrate improved capabilities for achieving high-precision fission fragment yield measurements.